(untitled) (Nexo Revista Científica, 2021)
The study area is located 5 km southwest of Mahdasht city in Karaj on the Urmia-Dokhtar magmatic arc. In this area, Eocene volcanic and pyroclastic rocks are observed including basaltic andesite lavas, andesite, Trachyandesiticand trachyte lavas, tuff, and ignimbrite, along with plutonic rocks. There are two spectra of basic and acidic for the rocks in the area, of which basic rocks are chemically calc-alkaline in nature.Among the signs of subduction rocks in the area are enrichment in the Ta, Nb, and Ti lavas, as well as the anomaly of the HFSE index relative to the LILE of incompatible elements content. The geochemical and petrogenetic studies indicate the origin of the area’s plutonic rocks and the role of differential crystallization accompanied by the crustal rocks-contamination and digestion of magma in the evolution of the magma forming these rocks. This magma has been originated from the low-grade partial melting of an enriched mantle origin beneath the continental lithosphere with the lherzolite garnet composition at a depth of 100 to 110 km in a post-collision tensile environment. Investigating the fluids involved in the region, the homogenization temperature with the temperature of copper veins formation is between 120 to 306 ° C, with the salinity percentage varying between 6.45 to 15.96% of sodium chloride weight. Accordingly, this metamorphic hydrothermal orebodyis located in the mesothermal category. The presence of sub-faults, joints, and cracks in the host rock has provided a low-pressure environment for a proper place for copper mineralizationas veins.